Gender Discourse in Islamic Family Law Between Text and Context - Dewi, Erna; Nur, Syamsiyah; Hasibuan, Badai; Ichsan, Muhammad (Alhurriyah, 2025)
Islam does not differentiate between men and women, skin color, or any other natural differences. In practice within society, women bear dual responsibilities such as cooking, washing, raising children, taking care of their husbands, and providing sexual services. In addition to earning a living and doing household chores, women also participate in activities. Women are viewed negatively if they neglect household responsibilities. Author's finding: that men only have one responsibility to earn a living, which certainly does not compare to women who do many things. This research uses literature study and qualitative field study. The findings and discussions include a review of qualitative research methods, literature studies, and field studies as a whole, or a combination of both. Furthermore, the data is analyzed using critical analysis techniques. The novelty in this research is "the ideal family relationship structure and gender equality through the cooperation of men and women." In families, gender partnership encompasses aspects such as the division of roles and tasks, transparency, accountability, and good governance. By following Islamic discourse, gender partnership can establish fair and equal gender relationship patterns in family life. This will prevent injustice or harm in the form of an inability to perform family duties.